Deficiency of Mitochondrial Functions and Peroxidation of Frontoparietal Cortex Enhance Isoflurane Sensitivity in Aging Mice - Gong, Cansheng; Zhang, Donghang; Ou, Wei; Ou, Mengchan; Liang, Peng; Liao, Daqing; Zhang, Weiyi; Zhu, Tao; Liu, Jin; Zhou, Cheng (Frontiers in Aging Neuroscience, 2020)
Background: Hypersensitivity to general anesthetics may predict poor postoperative outcomes, especially among the older subjects. Therefore, it is essential to elucidate the mechanism underlying hypersensitivity to volatile anesthetics in the aging population. Given the fact that isoflurane sensitivity increases with aging, we hypothesized that deficiencies of mitochondrial function and elevated oxidative levels in the frontoparietal cortex may contribute to the enhanced sensitivity to isoflurane in aging mice. Methods: Isoflurane sensitivity in aging mice was determined by the concentration of isoflurane that is required for loss of righting reflex (LORR). Mitochondrial bioenergetics of the frontoparietal cortex was measured using a Seahorse XFp analyzer. Protein oxidation and lipid oxidation in the frontoparietal cortex were assessed using the Oxyblot protein oxidation detection kit and thiobarbituric acid reactive substance (TBARS) assay, respectively. Contributions of mitochondrial complex II inhibition by malonate and peroxidation by ozone to isoflurane sensitivity were tested in vivo. Besides, effects of antioxidative therapy on mitochondrial function and isoflurane sensitivity in mice were also measured. Results: The mean concentration of isoflurane that is required for LORR in aging mice (14–16 months old) was 0.83% ± 0.13% (mean ± SD, n = 80). Then, the mice were divided into three groups as sensitive group (S group, mean − SD), medium group (M group), and resistant group (R group, mean + SD) based on individual concentrations of isoflurane required for LORR. Activities of mitochondrial complex II and complex IV in mice of the S group were significantly lower than those of the R group, while frontoparietal cortical malondialdehyde (MDA) levels were higher in the mice of S group. Both inhibition of mitochondrial complexes and peroxidation significantly decreased the concentration of isoflurane that is required for LORR in vivo. After treatment with idebenone, the levels of lipid oxidation were alleviated and mitochondrial function was restored in aging mice. The concentration of isoflurane that required for LORR was also elevated after idebenone treatment. Conclusions: Decreased mitochondrial functions and higher oxidative stress levels in the frontoparietal cortex may contribute to the hypersensitivity to isoflurane in aging mice.